2022
DOI: 10.3390/nu14235082
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Radish (Raphanus sativus L.) on Acetaminophen-Induced Liver Damage via Inhibiting Oxidative Stress and Apoptosis

Abstract: Alcohol and drug overdoses cause liver diseases such as cirrhosis, hepatitis, and liver cancer globally. In particular, an overdose of acetaminophen (APAP), which is generally used as an analgesic and antipyretic agent, is a major cause of acute hepatitis, and cases of APAP-induced liver damage are steadily increasing. Potential antioxidants may inhibit the generation of free radicals and prevent drug-induced liver damage. Among plant-derived natural materials, radishes (RJ) and turnips (RG) have anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(59 reference statements)
0
3
1
Order By: Relevance
“…However, our results didn't find a protective effect of black radish against benzyne harmful effect on liver, kidney, and spleen tissue in rats. This appears to be inconsistent with the results of other studies in which radish was found to protect rat livers, kidneys, and spleen against chemical toxicity [24,25]. The reason for this discrepancy might be due to the short period of treatment and the dose of the extract that we used in our study (100 mg/kg and 200 mg/kg body weight).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results didn't find a protective effect of black radish against benzyne harmful effect on liver, kidney, and spleen tissue in rats. This appears to be inconsistent with the results of other studies in which radish was found to protect rat livers, kidneys, and spleen against chemical toxicity [24,25]. The reason for this discrepancy might be due to the short period of treatment and the dose of the extract that we used in our study (100 mg/kg and 200 mg/kg body weight).…”
Section: Discussioncontrasting
confidence: 99%
“…Numerous phytochemicals with efficient antioxidant properties might also be promising antidotes [ 196 ]. As for NAC, these compounds might be able to protect against APAP-induced necrosis [ 17 , 197 ] and other possible types of cell death including necroptosis and apoptosis [ 198 , 199 ]. Furthermore, targeting autophagy, mitophagy and mitochondrial biogenesis could also be promising therapeutic strategies [ 22 , 195 , 200 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of herbal extracts may have similar hepatoprotective mechanisms. For example, CAS [162], radish extracts [153], dandelion extracts [159], Que Zui tea extract [46], PPRFs [203], and so on can all inhibit liver inflammation by activating the Nrf/HO-1 pathway. Different extracts from the same plants can activate different pathways and exert their respective effects.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Mechanistically, plant extracts exert their effects by enhancing antioxidant defense, inhibiting metabolism, and CYP enzymes to reduce the formation of NAPQI, stabilizing cell membranes and protecting hepatocytes, promoting liver regeneration, reducing inflammatory cytokines, decreasing cell apoptosis, and reversing liver morphology caused by APAP toxicity. For example, as mentioned in the table, radish extract exhibits antioxidant and anti-apoptotic effects by increasing the expression of Nrf-2 and HO-1 and regulating the function of BAX and BCL-2, thereby reducing APAP-induced toxicity [153]. Methanol extract of P. Chaba stem bark enhances the antioxidant capacity, inhibits NAPQI formation mediated by hepatic toxicity, accelerates the release of cytokines from the liver, thereby increasing phase II enzyme levels, and expedites the harmless metabolism [154].…”
Section: Natural Product Extractsmentioning
confidence: 99%